2021
DOI: 10.1093/tas/txab160
|View full text |Cite
|
Sign up to set email alerts
|

Significance of single β-mannanase supplementation on performance and energy utilization in broiler chickens, laying hens, turkeys, sows, and nursery-finish pigs: a meta-analysis and systematic review

Abstract: This review will give a brief description of β-mannans, abundance in feedstuffs, utility of supplemental feed β-mannanase and subsequent animal responses. Soybean products and co-products of processing palm, coconut and guar seeds are the major sources of β-mannans in poultry and livestock feed. β-mannans are linear polymers of mannose residues linked by β-1,4 glycosidic bonds and their ingestion elicit undesirable and metabolically costly responses. Web of Science was searched to retrieve published studies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 106 publications
1
14
0
Order By: Relevance
“…Protein feedstuffs are particularly rich in b-mannans, a type of hemicellulose rich in Dmannose units linked in b-(1-4) glycosidic bonds (Chen et al, 2018a). We recently reported the structure, abundance, and nutritional implications of b-mannans in common feedstuffs (Kiarie et al, 2021). In general, the major b-mannans in feedstuffs are glucomannan and galactomannan, and the concentration can be as high as 30% DM in some feedstuffs (Kiarie et al, 2021).…”
Section: Implications Of B-mannans On Gastrointestinal Physiology And...mentioning
confidence: 99%
See 2 more Smart Citations
“…Protein feedstuffs are particularly rich in b-mannans, a type of hemicellulose rich in Dmannose units linked in b-(1-4) glycosidic bonds (Chen et al, 2018a). We recently reported the structure, abundance, and nutritional implications of b-mannans in common feedstuffs (Kiarie et al, 2021). In general, the major b-mannans in feedstuffs are glucomannan and galactomannan, and the concentration can be as high as 30% DM in some feedstuffs (Kiarie et al, 2021).…”
Section: Implications Of B-mannans On Gastrointestinal Physiology And...mentioning
confidence: 99%
“…We recently reported the structure, abundance, and nutritional implications of b-mannans in common feedstuffs (Kiarie et al, 2021). In general, the major b-mannans in feedstuffs are glucomannan and galactomannan, and the concentration can be as high as 30% DM in some feedstuffs (Kiarie et al, 2021). Figure 1 illustrates the framework for gastrointestinal and ecology responses to intact feed b-mannans.…”
Section: Implications Of B-mannans On Gastrointestinal Physiology And...mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the findings of this study is the difference in ADFI during the growth period. In a meta-analysis on the effects of β-mannanase in different species, Kiarie et al [ 42 ] note that there is no difference for this parameter. The same authors observed a mean difference of 10.8 g/d, while in our study a difference of 74 g/d on behalf of CON in the growing period and 43 g/d for HC in the finishing period was observed.…”
Section: Discussionmentioning
confidence: 99%
“…FE in pigs is a complex trait with a large number of biological and environmental components. Environmental factors such as feed composition are constantly studied, leading to new understanding and advances in the optimization of feed composition (4,5). Furthermore, advancements in molecular biology techniques have led to many/several studies directed at identifying the biological components involved in FE in pigs.…”
Section: Introductionmentioning
confidence: 99%